Factors Influencing Purchase Intention for PIK House Properties in Jakarta - Billy Taniago; Rodhiah Rodhiah (International Journal of Management Science and Application, 2024)
This study investigates the influence of relationship marketing, trust, and corporate image on purchase intention for PIK house properties in Jakarta during a period of economic challenges marked by inflation and declining property sales. The research employed a quantitative approach with data collected through online questionnaires from 173 respondents in June 2024, utilizing non-probability sampling and judgemental sampling techniques. Analysis was conducted using PLS-SEM with Smart-PLS 4.0 software. The findings revealed that relationship marketing (path coefficient = 0.470, p-value = 0.000) and corporate image (path coefficient = 0.369, p-value = 0.000) have significant positive influences on purchase intention. However, trust showed no significant impact on purchase intention (path coefficient = 0.019, p-value = 0.811), potentially due to the demographic composition of respondents being predominantly students (90.2%). The model demonstrated strong explanatory power with an R-square value of 0.647, indicating that 64.7% of purchase intention variance is explained by the studied variables. These findings provide valuable insights for property developers in formulating marketing strategies, particularly emphasizing the importance of relationship marketing and corporate image in driving purchase intention for high-value properties.